STATE REGULATION OF INFORMATION SECURITY IN UKRAINE (Coordinates of Public Administration, 2026)
The scientific article examines the peculiarities of state regulation of information security in Ukraine under conditions of contemporary geopolitical transformations, societal digitalization, and the growing scale of information threats. It is substantiated that under modern conditions, information is becoming not only a strategic resource for social development but also an important instrument of political influence, a means of conducting hybrid confrontation, and a factor in ensuring national security. It has been established that information security is an important component of the public administration system, as its provision is directly related to the protection of national interests, maintenance of information sovereignty, and ensuring the resilience of the state's information environment. State regulation of information security is considered as a comprehensive managerial process aimed at establishing legal, institutional, and organizational mechanisms for protecting the information environment. It has been determined that contemporary processes of digital transformation, along with expanding opportunities for the use of information and communication technologies, generate new challenges related to the dissemination of disinformation, information manipulation, cyber threats, interference in the functioning of state information systems, and violations of personal data security. Particular attention is paid to the analysis of legal mechanisms for ensuring information security and the institutional aspects of implementing state policy in this area. The necessity of systematically improving the legal and regulatory framework in accordance with the challenges of the modern digital environment, as well as strengthening coordination among public administration bodies, is substantiated. The importance of enhancing interagency cooperation, international collaboration, and the implementation of modern digital technologies in the field of information space protection is emphasized. It is concluded that effective state regulation of information security requires a comprehensive combination of legal, institutional, and technological mechanisms aimed at ensuring state resilience under contemporary information challenges.